(untitled) (Research, Society and Development, 2021)
The zygoma is a pyramidal bone that has a thick body and four processes, the temporal, orbital, maxillary and frontal. These processes are the weak points of this bone. The treatment of fractures of the zygomatic complex can be performed in an open or closed way. A conservative technique widely used and effective is the use of Gancho de Barros, its biggest advantage is the speed and efficiency in the reduction. Male patient, leucoderma, 52 years old, attended the Hospital da Restauração in Recife / PE, with a history of physical aggression on the left side, with fractures in the bones of the face (zygomatic-orbital complex in the left side), zygomatic arch on the left side, maxilla and orbit (Blow-out) on the left side. The treatment established was anatomical reduction using the Gancho de Barros. The closed reduction with Gancho de Barros in this specific case, proved to be a safe and reliable device, with a good prognosis and without observation of complications and post-operative sequelae.